Strategies of Counseling and Guidance Teachers and Schools in Dealing with Student Delinquency - Rizal, Syamsul (International Journal of Education Research and Development, 2023)
Delinquency is behavior or actions that can violate moral values, rules, cause problems that can harm oneself and others. The problem at SMP Negeri 2 Rejang Lebong is that there is delinquency committed by some students both in terms of association with fellow friends, the environment and actions and actions that are not good during learning hours. So this study aims to determine  the teaching and learning process of students at SMP Negeri 2 Rejang Lebong and  the strategies of guidance and counseling teachersto overcome delinquency in SMPNegeri 2 Rejang Lebong. This type of research is descriptive qualitative with data collection techniques using observation, interview and documentation methods. The main data were obtained from the principal, counseling guidance teacher and students of SMP Negeri 2 Rejang Lebong. The results  of this study  are that first, the form of student delinquency at SMP Negeri 2  Rejang Lebong in general, noisy and quarreling in class, like to skip classes and smoke, like to be noisy in class, wear clothes that are not in accordance with the rules at school, and have problems or enemies with their friends. Second, strategies carried out by schools to reduce student delinquency include prevention strategies, including cooperation with parents and the community around the school.